HUBUNGAN LINGKAR KEPALA BAYI BARU LAHIR DAN KENAIKAN BERAT BADAN IBU SELAMA HAMIL DENGAN KEJADIANRUPTUR PERINEUM DI BPM “Z” BENGKULUTAHUN 2014 - Ratna Dewi (Jurnal Ilmu Kesehatan Masyarakat, 2017)
The incidence of ruptur in Indonesia which is only about 5% of all deliveries in Indonesia. The most important cause of maternal mortality in Indonesia is 40-60% of bleeding, including bleeding because of the birth canal laceration 4-5%. Objective of this study was to determine the relationship head circumference of newborns and maternal weight gain during pregnancy with rupture of the perineum in BPM Z.type of research is analytic with case control study design. The population in this study all mothers who gave birth in BPM "Z" in 2013 which amounted to 160 people, with 32 people taken in the case of total sampling and control as many as 32 people and taken by systematic random sampling. Data collected were analyzed by chi-square test. The results showed, obtained 64 respondents, birth mothers with rupturperineum 32 (50%) occur in mothers who gave birth to the size of head circumference> 34cm (71.9%), and pregnant women who experience weight gain> 12.5 ( 75.0%). Results of analysis for head circumference obtained by the P value 0.003 OR 5.622. The results of the analysis of maternal weight gain obtained P 0.003 OR 5.727. This means that there is a significant relationship between head circumference of newborns and maternal weight gain during pregnancy with ruptur of the perineum. Advised pregnant women need to do a routine check of at least four times during pregnancy, in order to be pursued maternal weight gain is within the normal enhancement. Keywords : Head circumference of newborn, maternal weight gain during pregnancy, Ruptur of the perineum